Women, literature and development in Africa - Kalu, Anthonia C. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book is a powerful exploration of the role of women in the evo lution of African thinking and narratives on development, from the prec olonial period right through to the modern day. Whilst the book identif ies women's oppression and marginalization as significant challenges to contemporary Africa's advancement, it also explores how new written na rratives draw on traditional African knowledge systems to bring deep-ro oted and sometimes radical approaches to progress. The book asserts tha t Africans must tell their own stories, expressed through the complex m eanings and nuances of African languages, and often conveyed through or al traditions and storytelling, in which women play an important role. The book's close examination of language and meaning in the African nar rative tradition advances the illumination and elevation of African sto rytelling as part of a viable and valid knowledge base in its own right , rather than as an extension of European paradigms and methods. Anthon ia Kalu's new edition of this important book, fully revised throughout, will also include fresh analysis of the role of digital media, educati on and religion in African narratives. At a time when the prominence an d participation of African women in development and socio-political deb ates is growing, this book's exploration of their lived experiences and narrative contribution will be of interest to students of African lite rature, gender studies, development, history, and sociology"--
Introduction -- The African Woman and African Literary Criticism -- African Literary Theory and Research -- Paradigms of Tradition and Mode rnity: (Re)Centering Women in African Literature -- Nwanyibuife: Women and the Social Construction of Gender in African Development -- Languag e and Development in Africa -- Ala: Gendered Space and Development in A frica -- Women, Narrative Traditions and African Religious Thought -- C ultural Translations and Education in Africa.
Includes bibliographical references and index.
Keywords: African literature (English) -- Women authors -- History and critici sm; Women and literature -- Developing countries; Women and literature -- Africa; Women in economic development -- Africa; Developing countries -- In literature